Is the German Mittelstand more resistant to crises? - Michael Berlemann; Vera Jahn; Robert Lehmann (Small Business Economics, 2021)
In a globalized world with high international factor mobility, crises often spread quickly over large parts of the world. Politicians carry a vital interest in keeping crises as small and short as possible. Against this background we study whether the type of company of owner-managed SMEs, in Germany well-known as Mittelstand firms, helps increasing an economy's crisis resistance. We study this issue at the example of the Great Recession of the years 2008/2009. Using micro panel data from the ifo Business Survey, we study the comparative performance of Mittelstand enterprises and find supporting evidence for the hypothesis that Mittelstand firms performed more stable throughout the Great Recession than non-Mittelstand firms. We also show that owner-managed SMEs performed significantly better than SMEs and owner-managed large enterprises. Thus, it is rather the combination of firm size and owner-management that leads to more crisis resistance.
Keywords: E31; G12; 330; Mittelstand firms; Great Recession; Crisis resistance